Terpenoids as Cytotoxic Compounds: A Perspective - Prakash, Ved (Pharmacognosy Reviews)
Natural products serve as safe and effective therapeutic agents for the drug discovery. Plants produce bioactive secondary metabolites such as terpenoids, alkaloids, tannins, saponins, and others, which have profusely been studied for anti‑infective, anticancer, anti‑inflammatory potential, and metabolic disorders to name a few. Terpenoids constitute the largest class of natural compound. The study investigates the novel cytotoxic compound of the terpenoid family isolated from different natural sources. The anticancerous activities of the compounds discussed in this review are taken from the published articles showing activity against specific cancer cell lines. The compounds exclusively belong to terpenoid family. Considering the huge potential of plant‑based natural products in drug discovery program and the contribution of terpenoid in the production of anticancer compounds, it can be exploited for more reliable economical and environmentally safe bioactive molecules.
Keywords: Anticancer medicinal plant; natural source; phytochemical; terpenoids